NEW TUTORS’ PERSPECTIVE ON MOODLE PERFORMANCE: A CASE STUDY IN UNIVERSITAS TERBUKA - Siti Hadianti (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
The purpose of this study was to investigate the perspective of new tutors using Moodle at the Universitas Terbutka (UT).This study uses a qualitative method with a case study design. The research informants were seven new UT lecturers with different educational backgrounds. Researchers used a questionnaire to investigate new tutor perspectives on Moodle's performance. The questionnaire is closed which consists of 8 questions. In the questionnaire, the researcher modified the questions by classifying the range of responses with 5 scales: strongly agree, agree, doubt, disagree, strongly disagree. In applying the questionnaire, the researcher took two steps. First, researchers distributed questionnaires to study participants. Second, researchers began to extract, analyze, and conclude the data that had been collected using a questionnaire. In extracting data from the questionnaire, the researcher developed an analytical method based on Dey's theory which consists of describing phenomena, classifying them, and seeing how our concepts are related.The results reveal that there are three main things in relation to the new tutor's perspective: friendly to use, simple modification features, and convenient assessment tools. The results of this study are a major concern for tutors because this aspect is an important part that can support teaching and learning activities when using Moodle.